Hubungan Jenis Kanker dan Lama Pengobatan dengan Kualitas Hidup Anak Penderita Kanker di RSUD Dr. Moewardi Surakarta - Karunia Wulan Sari, Melita; Wahyudi, Totok; Agung Yudhianto, Kresna (Pustaka Galeri Mandiri, 2025)
Childhood cancer is the second leading cause of death after accidents among children aged 0–18 years and significantly impacts children’s quality of life, both physically, psychologically, socially, and spiritually. The type of cancer and duration of chemotherapy treatment are known to influence various aspects of children’s quality of life, including physical, emotional, social, and school functioning. In a previous study, 107 children (97%) were classified as having poor quality of life, while only 29 children (21%) had good quality of life.The purpose of this study is to analyze the relationship between the type of cancer and the duration of treatment with quality of life in children with cancer undergoing chemotherapy at Dr. Moewardi General Hospital in Surakarta. The research method used a quantitative approach with a cross-sectional design. The sample was selected using consecutive sampling among children with cancer undergoing chemotherapy. Data were collected using the PedsQL 4.0 cancer module questionnaire and analyzed using the bivariate Chi-Square statistical test. Results: The study results showed a significant relationship between cancer type and quality of life in children with cancer (p=0.028), as well as a significant relationship between treatment duration and quality of life in children with cancer (p=0.043). Children with solid cancers and those undergoing treatment for more than 6 months tended to have lower quality of life. Cancer type and duration of treatment significantly influence the quality of life of children with cancer. Therefore, special attention is needed in nursing approaches that consider both factors to improve the quality of life of children during chemotherapy.